AN EMPIRICAL STUDY ON SOCIO-ECONOMIC CONDITION AND WORKING PROBLEMS OF BRICK KILN WORKERS OF NORTH 24 PARGANAS, WEST BENGAL - Basu, Kamalika (ShodhKosh: Journal of Visual and Performing Arts, 2022)
Brick kiln workers in West Bengal represent a critical yet under-explored segment of the state's labor force, forming an essential component of the informal economy. Predominantly composed of seasonal migrants from marginalized communities, these laborers endure severe working conditions characterized by long hours, minimal wages, and hazardous environments. This research delves into the socio-economic realities of brick kiln workers, examining their patterns of migration, labor dynamics, and the structural inequalities they face. Utilizing a mixed-methods approach, the study draws on extensive fieldwork, including surveys and in-depth interviews, to provide a comprehensive understanding of the workers' lived experiences. The analysis reveals systemic exploitation, lack of social security, and a persistent cycle of poverty exacerbated by insufficient access to healthcare, education, and housing. Additionally, the research highlights the gendered dimensions of labor within kilns, where women and children often contribute to the workforce without formal recognition or adequate protections. The findings underscore the urgent need for policy interventions aimed at improving labor rights, ensuring occupational safety, and providing avenues for social mobility. By shedding light on the plight of brick kiln workers, this study calls for a re-evaluation of labor laws and advocates for the integration of these workers into broader development frameworks.